ORGANO PHOSPHORUS COMPOUND POISONING, COMPLICATED ACUTE RENAL FAILURE AND DELAYED POST HYPOXIC ENCEPHALOPATHY - A CASE REPORT - Babu S, Suresh; Badrinath, A K; Suresh, K; C, Debranjani (International Journal of Clinical and Biomedical Research, 2015)
Organophosphorus compound (OPC) poisoning is one of the most common poisons in rural India. We present a 27 year old female patient who came to us in altered sensorium and froathing from mouth with an alleged history of OPC intake about 2 hours back. The patient was intubated, connected to a mechanical ventilator and atropinized. On day 3 of admission patient had elevated renal parameters and was diagnosed as Acute Renal Failure due to acute tubular necrosis probably poison induced. On day 4 of admission she suffered an acute cardiac arrest and was resuscitated; following this she gradually improved and after 3weeks of intensive management her sensorium deteriorated. MRI Brain showed Diffuse Cerebral White Matter Leukodystrophy due to DEMYELINATION (Hypoxia induced). KEYWORDS: Organophosphorus compound poisoning; Acute renal failure; Demyelination; Leukoencephalopathy.